Genotype by environment interaction in Musa germplasm revealed by multisite evaluation in subSaharan Africa - Cauwer, I. de; Ortíz, R.; Vuylsteke, D.R. (1995)
A multilocational evaluation trial comprising 18 Musa genotypes was carried out from 1991 to 1994 in three representative locations in the humid forest (Onne, Nigeria and M'Balmayo, Cameroon) and the Forest-savanna Transstion (Ibadan, Nigeria) Zones of West and Central Africa. The main objective was to evaluate the performance of improved Musa germplasm under different agro-ecological conditions, thereby assessing the genotypes-by-environment interaction (GxE) for specific traits and yield stability. Hybrids, their parental genotypes together with plantain and banana landraces, were included in the trial for comparison purposes. Differences between the genotypes and environments were significant for all traits. Number of days to fruit filling was the only trait not affected by location effects. Due to a large number of fruits and high fruits weight, the improved germplasm showed heavier bunches than their parents, even though they had fewer hands. The GxE affected all traits, except fruit circumference. Genotypes-by-location effects were significant for bunch weight, number of hands, number of fruits and fruits weight. Most of the traits were not affected by genotype-by-cycle interaction at Onne and at Ibadan. These observations suggest that multilocational traits may be more efficient than single site trials over several years. Stability analysis of bunch weight and yield potential, based on the phenotypic coefficient of variation, allowed the identification of high and stable yielding genotypes, e.g. the black sigatoka resistant hybrids TMPx 1658-4 and TMPx 2796-5.